Karakter Religius Dalam al-Qur’an: Studi Analisis Tafsir Ayat-ayat Akhlak Dalam Al-Qur’an - Supriadi, Endi; Fitriana, Muhammad Azizan; Ulhaq, M. Ziyad; Isyanto, Nur (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2023)
Al-Qur'an as a holy book with three roles, namely as a guide (al-huda), an explanation of these instructions (al-bayyinah), and a distinction between rights and vanity (al-furqan), is a solution to deal with various problems that arise. in today's society. This research aims to. First, to find the concept of religiosity in the Qur'an. Second, looking for a relationship between the morals in the Qur'an and the cultivation of religious character. Third, enriching the treasures of Islamic scholarship regarding the values ​​of religiosity and morals. The method used in this study is a qualitative method that focuses on literature review with descriptive analysis that describes, explains and analyzes data in a detailed and informative manner. The research used comes from primary and secondary data including books of interpretation, both tahlili and maudhu'i, moral books both salaf and modern, books on science and technology and their implications as well as journals and websites that are relevant to the discussion. The results of this study can be concluded that there are many verses of the Qur'an relating to morals. The author only lists a few. The verses relating to these morals and their interpretations become standardization in the formation of religious character, by doing and getting used to things that are ordered or recommended and leaving everything that is prohibited by the Qur'an. With this standardization, religious character values ​​emerge, including: idealism, youth struggle and pioneering, having a pattern of logical and critical thinking, being responsible for actions, daring to accept punishment, youth's firmness in defending the faith, and so on.